(3GdCSS GdfXQjI hGdYdejIs - (3eMehO(B, (3GdThGhQgs ((3YeGf(B:s (3OGQ hGFd ddfTQ hGdJhRjY(B,s, 2008)
(3jJfGhd GdcJGH (B7 (3aUhd JVe adSaI hUaGJ heQJcRGJ heSDhdjGJ heSJhjGJ HhQUI GdGhQGb GdeGdjI hGdeYdheGJ GdedGFeg ddGSJKeGQ hGdJYQja HGdChQGb GdeGdjI hGdSfOGJ hGdGSge hfHPI YGeI Yf HhQUI YeGf hHjFI GdGSJKeGQ aj GdCQOf hGdefWdbGJ GdacQjI ddOQGSI GdJWHjbjI hGdeTGcd hGdaQVjGJ GdJj JhGLg GdOQGSGJ hJbhje GdGSYGQ GdShbjI hGdcaGAI aj JhRjY GdehGQO GdeJGMI Hjf GdbWGYGJ hZjQgG ef GdehVhYGJ GdeJYdbI HGdShb GdeGdj hQCS GdeGd hGdSjhdI hGdJOGhd(B. s
Keywords: (3GdChQGb GdeGdjIs; (3GdESJKeGQs; (3GdHhQUGJs